The Mediating Effect of Sustainability between Organizational Cloning and Organizations Performance in Manufacturing Industry - Al-Taie, Yousef H. (International Journal of Psychosocial Rehabilitation, 2020)
Organizational Cloning (OC) plays a key role in the progress and development of Organizations Performance (OP) by focusing on Sustainability (SU) as a mediator and, helping to increase equal opportunity and organizational development. The Iraqi Ministry of Industry is always interested in the good performance of industrial establishments and improving their manufacturing industry. A field study was conducted on Al-Kufa Cement Factory in Iraq. It is one of the most efficient plants in the production of cement, The Iraqi government is working on the construction of plants in other cities will be copied from the AL-Kufa Cement Factory. The questionnaire was distributed to 238 employees and 232 questionnaires were obtained and the respondent’s percent was 97%. The Likert 7 questionnaire was used and analyze statistical data by SPSS and SmartPLS and, was the result of the relationship between Organization Cloning (OC) and the Organizations Performance (OP) supported, r = 0.359, (r = 0.359, p > 0.05). There is significant mediator effect of Sustainability (SU) between (OC) and (OP) of supported. Factories in Iraq suffer from many problems and after reviewing the literature, there was a significant relationship between the factors of the cloning organization and organizations performance and Sustainability as a mediator. A number of previous studies have focused on how to eliminate the problems facing organizations. The purpose of this study is to suggest a framework on the impact of the organizational cloning on organizations performance. For the research methodology, the data will be collected from the employees of Kufa Cement Factory in Iraq. A base on the authors of the revised literature review framework of organizational cloning. Typically, future institutions will help to improve manufacturing industry.